The Akt–mTORC1 pathway mediates Axl receptor tyrosine kinase-induced mesangial cell proliferation. Issue 3 (4th July 2021) - Zhen, Yuxuan; McGaha, Tracy L; Finkelman, Fred D; Shao, Wen-Hai
Abstract: Glomerulonephritis (GN), an important pathologic feature of many renal diseases, is frequently characterized by mesangial cell proliferation. We and others have previously shown that the TAM family receptor tyrosine kinases Axl, Mer, and Tyro-3 contribute to cell survival, proliferation, migration, and clearance of apoptotic cells (ACs); that Axl contributes to GN by promoting mesangial cell proliferation; and that small molecule inhibition of Axl ameliorates nephrotoxic serum-induced GN in mice. We now show that stimulation of renal mesangial cell Axl causes a modest increase in intracellular Ca 2+ and activates NF-κB, mTOR, and the mTOR-containing mTORC1 complex, which phosphorylates the ribosomal protein S6. Axl-induction of Akt activation is upstream of NF-κB and mTOR activation, which are mutually codependent. Axl-induced NF-κB activation leads to Bcl-xl up-regulation. Axl is more important than Mer at mediating AC phagocytosis by mesangial cells, but less important than Mer at mediating phagocytosis of ACs by peritoneal macrophages. Taken together, our data suggest the possibility that Axl mediates mesangial cell phagocytosis of ACs and promotes mesangial cell proliferation by activating NF-κB and mTORC1. Graphical Abstract: Axl mediates mesangial cell phagocytosis of apoptotic cells and promotes mesangial cell proliferation by activating NF-kB and mTORC1.